A randomized controlled trial of acceptance and commitment therapy for psychological distress among persons with traumatic brain injury. Issue 7 (9th August 2021) - Sander, Angelle M.; Clark, Allison N.; Arciniegas, David B.; Tran, Kim; Leon-Novelo, Luis; Ngan, Esther; Bogaards, Jay; Sherer, Mark; Walser, Robyn
ABSTRACT: Psychological distress is common in persons with traumatic brain injury (TBI) but treatments remain underdeveloped. This randomized controlled trial of Acceptance and Commitment Therapy (ACT) was designed to address this gap. Ninety-three persons with medically-documented complicated mild to severe TBI, normal-to-mildly impaired memory, and clinically significant psychological distress in the chronic phase of recovery were randomized to receive eight weeks of ACT (manualized with adaptations to address TBI-related cognitive impairments) or a single session of needs assessment, brief counseling/education, and referral. The ACT group showed significantly greater reduction of psychological distress (Brief Symptom Inventory 18) and demonstrated improvements in psychological flexibility and commitment to action (Acceptance and Action Questionnaire-II (AAQ-II) scores). The number of treatment responders (post-treatment BSI 18 GSI T scores <63) was larger in the ACT group than in the control group. Entry of AAQ-II scores into the model of between-group differences in BSI 18 GSI T scores indicated that core ACT processes explained the variance in treatment group outcomes. Provision of ACT reduces psychological distress in persons with TBI in the chronic phase of recovery when adaptations are made to accommodate TBI-related cognitive impairments. Additional clinical trials with a structurally equivalent control group are needed.